Microstructural Characteristics of Fly Ash Geopolymer Modified Asphalt Binder - Bujang, Hazirah; Aman, Mohamad Yusri; Mohamad Taher, Mohammad Nasir; Suradi, Siti Samahani (uthm, 2023)
The incorporation of by-product materials, such as fly ash geopolymer, has a significant influence on the properties of asphalt binder. This results in a reduction in binder viscosity and an increase in binder stiffness. This, in turn, promotes enhanced aggregate-asphalt binder bonding. Geopolymer refers to a class of inorganic materials characterized by the formation of a long-range, covalently bonded non-crystalline skeleton. The aim of this study was to explore the potential of incorporating waste and by-product materials, specifically fly ash geopolymer additive, in order to influence the microstructure of asphalt binder. The focus was on examining how the inclusion of fly ash geopolymer could alter the internal arrangement and composition of the asphalt binder, leading to potential improvements in its properties and performance. Laboratory experiments were performed to analyze the microstructure of 60/70 and 80/100 asphalt binder samples using Scanning Electron Microscope (SEM) imaging. These samples were modified with various concentrations (3%, 5%, 7%, 9%, and 11%) of fly ash geopolymer additive. The SEM images were obtained to examine the morphological changes and assess the distribution of the fly ash geopolymer particles within the asphalt binder matrix at different additive concentrations. The NOVA NANOSEM 230 equipment was utilized to determine the morphological characteristics of the asphalt binders. The results showed notable variations in the properties of the asphalt binders modified with fly ash geopolymer compared to the unmodified control asphalt binder. The morphological evaluation revealed thorough blending of the fly ash geopolymer additive. Notably, the micrographs demonstrated a denser structure with increased percentages of fly ash geopolymer, indicating a presence of fly ash and alkaline activator promotes the rapid formation of polymerization. These findings emphasize the promising potential of fly ash geopolymer as an additive in asphalt binder. The significant effect it has on viscosity when incorporated into modified asphalt binder makes it a valuable candidate for application in the field.